Quality of life from oncological patients with definitive and temporary colostomy - Fortes,Renata Costa (2012)
INTRODUCTION: Colorectal cancer is one of the most prevalent neoplasms in the western world. Colostomy, temporary or permanent, can be a serious limiting factor affecting the quality of life of oncological patients. OBJECTIVE: To compare the quality of life of oncological patients with definitive and temporary colostomy. METHODS: Descriptive cross-sectional study carried out at a public hospital in Brasilia, Federal District of Brazil. The study analyzed 39 patients with colorectal cancer, 76.9% males, sorted into two groups: definitive ostomy (n=26) and temporary ostomy (n=13). The World Health Organization Quality of Life (WHOQOL)-bref questionnaire was used to assess the quality of life. Data were analyzed using Excel 2007 and Statistical Package for Social Sciences 19.0. RESULTS: 50% of definitive and 76.9% of temporary ostomy patients reported that the physical pain did not interfere in the affairs. 38.5% of definitive and 46.2% of temporary ostomy accepted their physical appearance. 46.2% of definitive and 53.8% of temporary ostomy reported good quality of life. 84.6% of definitive and 46.2% of temporary ostomy did not enjoy their life. 50% of definitive and 53.8% of temporary ostomy were satisfied with their sleep. 57.7% of definitive and 53.8% of temporary ostomy considered the environments as healthy. Over 70% of definitive and over 50% of temporary ostomy had financial constraints and were dissatisfied with leisure opportunities, respectively. 69.2% of definitive and 46.2% of temporary ostomy presented lower libido. 88.5% of definitive and 61.5% of temporary ostomy attended the church. CONCLUSION: The results showed that temporary ostomy patients suffer the same afflictions as the patients with definitive ostomy, equally affecting the quality of life of these patients.